Types of Interjection (A Descriptive Analysis in Dragon Ball Super English Comic Book) - Willyana Ramlan; Yana Putra Triana; Ferany Shaily Maulida (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2019)
The aims of the study are to describe the types and function of the interjection contained in the comic